PERANCANGAN PENILAIAN KINERJA KARYAWAN BERDASARKAN KOMPETENSI SPENCER DENGAN METODE ANALYTICAL HIERARCHY PROCESS(Studi Kasus di Sub Dinas Pengairan Dinas Pekerjaan Umum Kota Probolinggo) - Eko Nurmianto; Nurhadi Siswanto (Institute of Research and Community Outreach - Petra Christian University, 2006)
In this research, Worker Performance Appraisal System has been conducted in the Public Worker Council Probolinggo. This research especially conducted in the Sub Public Worker for Low Level Workers, i.e. Contract Workers. So far incentive in this institution was not given based on their performance, but based on the community agreement. Therefore, the worker performance appraisal system was designed based on the competency, namely the Spencer competency. For that purpose the Spencer appraisal Dimension has been integrated to DP3 (Daftar Penilaian Pelaksanaan Pekerjaan) and to the Competencies for the Executive Leadership Development. The results on those criterias were processed using the Expert Choice Software. The weight for the managerial skill is 0.200 and for the technical one is 0.800. Type of managerial skill is indicated by the competency criteria, i.e, discipline, serving, achievement, proactive and commitment to organization. The weights of each criterion are 0.318, 0.289, 0.151, 0.140, 0.102, respectively. On the other hand, Technical skills indicated by competency criteria are leadership and cooperation. Their weights are 0.500, 0.500, respectively. It can be concluded that, the accurate incentive system is an insentive system, based on profit share. This share is given according to the performance appraisal of each worker. Abstract in Bahasa Indonesia : Penelitian ini membahas tentang sistem penilaian kinerja karyawan yang dilakukan di Dinas Pekerjaan Umum Kota Probolinggo, khususnya Sub Dinas Pengairan untuk karyawan level bawah (karyawan kontrak). Selama ini pemberian insentif di Sub Dinas tersebut tidak didasarkan atas kinerja karyawan tetapi atas dasar kebersamaan/ gotong royong. Untuk meningkatkannya dirancang sistem penilaian kinerja karyawan berbasis kompetensi, khususnya kompetensi Spencer. Dimensi penilaian Spencer diintegrasikan dengan DP3 dan Competencies for Executive Leadership Development. Kriteria diolah dengan Software Expert Choice. Hasilnya bobot kemampuan karyawan kontrak terbagi atas: kemampuan manajerial (0.200) dan kemampuan teknik (0.800). Kemampuan manajerial terdiri dari: disiplin (0.318), melayani (0.289), berprestasi (0.151), proaktif (0.140), dan komitmen pada organisasi (0.102). Sedangkan kemampuan teknis terdiri dari: memimpin (0.500) dan kerjasama (0.500). Dari penelitian tersebut sistem insentif yang tepat adalah sistem insentif pembagian laba, dimana insentif yang diterima berdasarkan pada peningkatan kinerja karyawan. Kata kunci: penilaian kinerja karyawan, kompetensi, insentif, analytical hierarchy process.